Clinical Effects of Subgingivally Delivered Spirulina Gel in Chronic Periodontitis Cases: A Placebo Controlled Clinical Trial - Mahendra, Jaideep (JCDR Research and Publications (P) Limited, 2013)
Aims and Objectives: The aim of this study was to assess the clinical effects of Spirulina in-situ gel as an adjunct to Scaling And Root Planning (SRP) in the treatment of chronic periodontitis subjects. Material and Methods: 64 sites were selected with probing pocket depth of ≥5mm and they were divided into 2 groups; 33 sites were treated with SRP along with spirulina gel (Group A) and 31 sites were treated with SRP alone (Group B). Clinical parameters were recorded at baseline before SRP and at 120(th) day after the treatment therapy. The parameters included Probing Pocket Depth (PPD) and Clinical Attachment Level (CAL). Results: Both the groups showed significant improvement in the parameters. However, Group A (SRP along with spirulina) showed statistically significant decrease in mean probing pocket depth and gain in the clinical attachment level after 120 days as compared to Group B SRP alone. Conclusion: Locally delivered spirulina gel, along with scaling and root planning, has been shown to cause a beneficial impact. The efficacy of the product as a local drug delivery system in the non-surgical treatment of periodontitis without any side effects has been proved. Spirulina appears to be promising. It exerts strong anti-inflammatory effects which are closely connected with its antioxidative activity. This study can have a significant impact on the treatment procedures of periodontitis, with the use of blue green algae in the future.